Analysis Of Transformer Reliability And Loading At The New Cirata 150kv Substation - Muhammad Daud Rizky Siregar; Dino Erivianto; Rahmaniar Rahmaniar (Jurnal Media Computer Science, 2026)
Transformers are critical components in power transmission systems that require regular reliability monitoring and load analysis to ensure optimal operation. This study analyzes the reliability and load characteristics of a 60 MVA power transformer at the Cirata Baru 150kV substation using operational data from July 2025. The research methodology used a quantitative approach with SCADA data analysis and graphical visualization. The analysis results show that the transformer operated with an average load of 19.75 MVA (32.91% loading) and a peak load of 20.40 MVA (34% loading) which occurred on July 17, 2025, at 19:00 WIB. The average power factor reached 96.52%, indicating excellent system efficiency. The average operating current was recorded at 551.77 A with a stable operating voltage of 20.49 kV. The transformer's capacity margin of 39.60 MVA (66%) provides ample room for future load growth. Load growth projections assuming 5% per year indicate that the transformer has sufficient capacity to serve needs for at least the next 15 years. Operational conditions well below nominal capacity provide high reliability and a long economic life.